Curcumin and vinblastine induce apoptosis and impair migration in human cutaneous melanoma cells (Research, Society and Development, 2022)
Cancer is an important cause of lethality, and melanoma is associated with less than 10% of survival. The traditional treatment includes the use of vinblastine, and it is associated with side effects. Curcumin is extracted from Curcuma longa rhizomes, and studied in many diseases, producing a variety of effects. We investigated the role of various cellular pathways concerning apoptosis, cell cycle enzymes in melanoma cell line SK-MEL-28, after treatment with curcumin, vinblastine, or a combination of both, for 24 hours. After this, we performed cell cycle, apoptosis, wound healing assay, comet assay on cells, and evaluated nitrite accumulation (nitric oxide (NO•) byproduct). Curcumin increased cells in apoptosis and reduced the number of cells in the G1 phase. Vinblastine increased the production of nitrite, and cells in early apoptosis, mainly through the inducement of DNA damage. Cell migration was impaired in all tested groups. In conclusion, curcumin impaired migration, producing NO•, and promoting apoptosis of tumoral cells. Vinblastine also impaired cell migration and increased levels of NO•. Curcumin might be included as an adjuvant in the treatment of melanoma, and help treatment of melanoma, and further studies are needed, especially regarding the synergistic effect of curcumin and vinblastine in the treatment.